Golosina canibal 2.0: Antropofagia, transculturación, migraciones y banquetes en la literatura argentina reciente - Nespolo, Maria Jimena (2018)
This article offers a reading of the novel El Entenado (1982) by Juan José Saer, analysing the way in which it is inserted within the author’s system and within the Argentinean literary canon. The Saerian heritage is resignified by cannibalism and its presence in cultural studies. ‘Cannibalism’ stresses a relativised opposition between interior and exterior by founding an exuberant de-colonial polysemy that challenges the stigma of savagery and barbarism with which classical historiography has characterised the New World. The cannibal cleavage of texts published after the year 2000 – texts singularly crossed by the migration experience – plays with a culture of knowledge and flavour, eating and being-eaten.